Life Cycle Perspective of R&D Investment Management: Case Study Approach - Marie Kubáňková; Jaroslava Hyršlová (European Financial and Accounting Journal, 2014)
The management of R&D activities has become popular among researchers. The need for changes in R&D organization and financial support brings new decision-making issues for the R&D manager. Life cycle concepts help to manage R&D in the whole perspective. The aim of this paper was to examine the life cycle costing for R&D investment appraisal. A case study was realised in a private SME company for the R&D project of the bumblebee laboratory production. The analysis showed the possibility of using life cycle product perspective to control R&D investment. The expenditure was compared to the net income generated during the whole life cycle of the product. This complex evaluation allows to meet the requirements of the R&D management and to support the decision-making process. Using the life cycle perspective the company will gain a tool that will give an evaluation of the R&D's effectiveness and provides an opportunity to manage R&D projects and compare them with others investments.
Keywords: M21; 650; Life Cycle Costing; R&D investment; Strategic Management Accounting